The banking system and its role in the development of the country`s economy - Ding Xiaoyan (Kharkiv : V. N. Karazin Kharkiv national university, 2024)
The object of the banking system of Ukraine. The subject of the study is modern approaches and methods for analyzing the banking system's role in Ukraine's economic development, focusing on its structural components and stability. The purpose of the qualifying master's thesis is theoretical generalization and analysis of the banking system’s role in Ukraine's economic development, emphasizing its contribution to financial stability, regulatory reforms, and macroeconomic performance. The study employs systematic approaches to assess the structural components, historical evolution, and impact of reforms in the Ukrainian banking system. The tasks of the qualifying master's thesis are: to investigate theoretical approaches to the role of banking systems in economic growth and their adaptation to Ukraine's context; to analyze Ukraine’s regulatory framework and its influence on banking system stability; to evaluate financial and operational performance indicators of the banking sector; to explore the dynamics of non-performing loans (NPLs) and their impact on financial stability; to assess the adoption of modern banking technologies and their role in promoting financial inclusion; to conduct experimental research, including stress testing and macroeconomic modeling, to assess resilience and challenges in Ukraine’s banking sector; to develop recommendations for improving corporate governance, regulatory frameworks, and risk management in the Ukrainian banking system. According to the results of the research, theoretical and practical recommendations focusing on enhancing financial stability, reducing systemic risks, and improving the resilience of the banking system in Ukraine. The recommendations also include strategies for adopting digital transformation, improving macroprudential regulation, and fostering financial inclusion to support economic development. The obtained results can be applied to develop macroeconomic strategies, policy-making processes, and institutional frameworks to strengthen Ukraine's banking system according to international standards.
Банківська система та її роль у розвитку економіки країни
Scientific advisor: Baranova Valeriia, doctor of economics, professor, departament banking business and financial technologies
Keywords: SOCIAL SCIENCES::Business and economics::Business studies; banking system; economic development; financial stability; non-performing loans; regulatory framework; digital transformation